Conolophus marthae sp.nov. (Squamata, Iguanidae), a new species of land iguana from the Galápagos archipelago - Gentile, Gabriele; Snell, Howard (Zootaxa, 2009)
Conolophus marthae sp. nov., a new species endemic to Volcan Wolf of northern Isla Isabela of the Galápagos archipelago, is described. The new species is morphologically, behaviorally, and genetically distinguished from the other two congeneric species C. subcristatus and C. pallidus. Besides the taxonomic implications, C. marthae sp. nov. is extremely important as it is the only evidence of deep divergence within the Galápagos land iguana lineage.